THE ROLE OF HUMAN RESOURCE MANAGEMENT IN ENHANCING EMPLOYEE PERFORMANCE AND ORGANIZATIONAL SUCCESS - Savitha S; Aswathanarayana K (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Human Resource Management (HRM) plays a crucial role in the success of modern organizations by ensuring that employees are effectively recruited, trained, motivated, and retained. This study explores the impact of HRM practices on employee performance and organizational success, focusing on recruitment, training, performance management, compensation, and engagement strategies. The research adopts a mixed-methods approach, using primary data from HR professionals and secondary data from academic sources. Findings indicate that well-structured HRM strategies contribute significantly to employee productivity, retention, and organizational competitiveness. However, HRM also faces challenges such as talent retention, workforce diversity, and the integration of technology. The study concludes with recommendations on HR policies, strategic workforce planning, and digital HR transformation.